Impact of exercise training in a hypobaric/normobaric hypoxic environment on body composition and glycolipid metabolism in individuals with overweight or obesity: a systematic review and meta-analysis - Liu, Peng; Chen, Hao; Jiang, Xin; Diaz-Cidoncha Garcia, Jorge (Frontiers in Physiology, 2025)
ObjectiveThis study aims to assess the impact of hypoxia training on body composition and glycolipid metabolism in excess body weight or living with obese people through meta-analysis.MethodsRandomized controlled trials investigating the effects of hypoxia training on body composition, glucose, and lipid metabolism in excess body weight or living with obese people were systematically searched from databases including CNKI, PubMed, and Web of Science. The meta-analysis was performed by using Stata 18 and RevMan 5.4 analytic tools. The risk of bias was assessed using the Cochrane evaluation tool, and the level of certainty of evidence was determined by the GRADE framework. Between-study heterogeneity was examined using the I2 test, and the publication bias was evaluated via the Egger test or funnel plot.ResultsA total of 32 RCTs with 1,011 participants were included. A meta-analysis of 25 RCTs was performed (499 men and 480 women, Age: 40.25 ± 15.69, BMI: 30.96 ± 3.65). In terms of body composition, the outcome indexes of body fat ratio (MD is −1.16, 95% CI -1.76 to −0.56, P = 0.00) in the hypoxia group were better than the normal oxygen group. There was no significant difference in body mass and BMI between the hypoxia group and the normal-oxygen group (P > 0.05). In terms of lipid and glucose metabolism, no significant changes were found between the hypoxia group and the normoxia group (P > 0.05). Subgroup analysis showed that training in hypoxic environment at altitude 2001–2,500 m could effectively improve body mass, TG and LDL-C (P < 0.05). The effective program to reduce body mass is to carry out moderate intensity training of 45–60 min for ≤8 weeks, ≥4 times a week (P < 0.05).ConclusionHypoxic training is essential for reducing body fat ratio in excess body weight or obese people. It is recommended to carry out 45–60 min of moderate-intensity aerobic exercise for ≤8 weeks, ≥4 times a week, in a hypoxia environment of 2,001–2,500 m to lose body mass. The effects of hypoxia training and normoxia training on lipid and glucose metabolism in excess body weight or obese people are the same.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024628550